Re-engaging 'youth at risk' of disengaging from schooling through rugby league club partnership: unpacking the pedagogic practices of the Titans Learning Centre. Issue 4 (4th May 2018) - Whatman, Susan L.; Main, Katherine
ABSTRACT: The youth learning re-engagement program known as the Titans Learning Centre (or TLC) is an approved alternative schooling program, developed in partnership with state education and a local National Rugby League (NRL) club, the 'Titans'. Students typically in Grade Three or Four complete a 10 week program, interacting with professional A grade NRL players on a weekly basis during classroom learning time and lunch time 'handball' sessions. The project sought to understand the pedagogic practices of the TLC, using Bernstein's social construction of pedagogic discourse, with its underlying instructional and regulative discourses, particularly the contribution by the players to what and how the students were learning. The ethical consent of recruiting children to the study was achieved via acceptance of a position in the program for classroom observations, with further consent sought for accessing students' school performance data, student and parent surveys and interviews. Using case study methodology, Productive Pedagogies classroom audits ( n  = 26) were adapted for classroom observation. Interviews with relevant program stakeholders were conducted, including players ( n  = 12), NRL game development staff ( n  = 1) and teachers and teacher aides ( n  = 4). The findings revealed the pedagogic approaches of teachers and NRL players emphasised making regulative discourses visible to these young learners, developing supportive classroom environments and building students' sense of connectedness to learning. The players articulated a genuine sense of contribution to the lives of the young learners and saw themselves as role models. The use of high profile athletes in youth re-engagement programs has been questioned in recent times, particularly their effectiveness in terms of student learning outcomes over time. However, we conclude that the depth of involvement in pedagogic action connected to student learning indeed enabled the NRL players to be considered role models for youth re-engagement in learning.